2021
DOI: 10.1186/s40798-021-00341-7
|View full text |Cite
|
Sign up to set email alerts
|

Maximal muscular power: lessons from sprint cycling

Abstract: Maximal muscular power production is of fundamental importance to human functional capacity and feats of performance. Here, we present a synthesis of literature pertaining to physiological systems that limit maximal muscular power during cyclic actions characteristic of locomotor behaviours, and how they adapt to training. Maximal, cyclic muscular power is known to be the main determinant of sprint cycling performance, and therefore we present this synthesis in the context of sprint cycling. Cyclical power is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 230 publications
2
42
0
Order By: Relevance
“…These fatigue-induced changes can be described by a parallel shift in the F/v profile towards the origin [29,30]. Power output declines in an approximately exponential fashion as a result of increasing fatigue when performing maximal exercise to exhaustion [1,2]. In accordance, we found that the time course of the shift in the F/v profile with fatigue is also exponential.…”
Section: Physiological Modelsupporting
confidence: 81%
See 3 more Smart Citations
“…These fatigue-induced changes can be described by a parallel shift in the F/v profile towards the origin [29,30]. Power output declines in an approximately exponential fashion as a result of increasing fatigue when performing maximal exercise to exhaustion [1,2]. In accordance, we found that the time course of the shift in the F/v profile with fatigue is also exponential.…”
Section: Physiological Modelsupporting
confidence: 81%
“…In the 500 m and 1000 m-time trials, athletes usually use a standing position in the initial phase (acceleration phase) and a seated position at high speed [2].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been suggested that approximately ∼80–85% of the power produced over a pedal cycle is generated during leg extension (i.e., the downstroke), whilst ∼15–20% is produced during leg flexion (i.e. the upstroke) [ 26 ], which may also explain the significant roles of TA, RF, and VAS during sprint cycling. In a broader context, these findings indicate that the anaerobic endurance training of HAM and SOL for improving 30-second all-out sprint cycling exercise performance and the whole anaerobic endurance ability of lower limb muscles is less of a concern as the two muscles are not apt to fatigue during exercise.…”
Section: Discussionmentioning
confidence: 99%